Answer:
6 C(s) + 3 O₂(g) + 2 Fe₂O₃(s) → 4 Fe(s) + 6 CO₂(g)
Step-by-step explanation:
Iron can be formed in two steps.
Step 1: 2 C(s) + O₂(g) → 2 CO(g)
Step 2: Fe₂O₃(s) + 3 CO(g) → 2 Fe(s) + 3 CO₂(g)
In order to get the net chemical equation, we will multiply the first step by 3, the second step by 2, and then add them.
6 C(s) + 3 O₂(g) → 6 CO(g)
+
2 Fe₂O₃(s) + 6 CO(g) → 4 Fe(s) + 6 CO₂(g)
--------------------------------------------------------------------------------------------------
6 C(s) + 3 O₂(g) + 2 Fe₂O₃(s) + 6 CO(g) → 6 CO(g) + 4 Fe(s) + 6 CO₂(g)
6 C(s) + 3 O₂(g) + 2 Fe₂O₃(s) → 4 Fe(s) + 6 CO₂(g)